Exploring the Impact of Aistear on Montessori. - Gilpin, Jayne (STER, 2020)
The purpose of this article is to explore the impact of implementing Aistear: The Early Childhood Curriculum Framework (NCCA, 2009) on Montessori education. It also examines the extent to which Aistear and Montessori can be integrated successfully. It presents some evidence that current Early Years (EY) regulations have the potential to create a monopoly of Aistear play based services, and that increased reliance on government funding could cause an imbalance of power between the inspector and the provider that undermines the Montessori approach.
Journal article
Keywords: Research Subject Categories::SOCIAL SCIENCES; Curriculum; Montessori; Aistear; Integration; Implementation; Inspections